Correction: Enantioselective synthesis of sulfoxide using an SBA-15 supported vanadia catalyst: a computational elucidation using a QM/MM approach. Issue 2 (15th December 2017) - Kaur, Navjot; Gupta, Shuchi; Goel, Neetu
Abstract : Correction for 'Enantioselective synthesis of sulfoxide using an SBA-15 supported vanadia catalyst: a computational elucidation using a QM/MM approach' by Navjot Kaur et al., Phys. Chem. Chem. Phys., 2017, 19, 25059–25070.